Ciprofloxacin is not a better choice in the patients with diabetes suffering urinary tract infection - Uğur, Kader; Bal, İsa Ahmet; Tartar, Ayşe Sağmak; Gozel, Nevzat; Orhan, Bedrettin; Dönder, Emir; Özercan, Abdullah Mübin (My University, 2019)
Objective: The aim of this study is to determine antibacterial susceptibilities of Gram-negative bacteria isolated fromdiabetic and non-diabetic patients as infectious agents of community-acquired urinary tract infections (UTI) and tocompare their rates of resistance to the antibiotics frequently used in empirical treatment.Methods: Ninety-six diabetic and sixty-eight non-diabetic (total n=164) patients’ data were evaluated retrospectivelywho diagnosed as community-acquired urinary system infection and consulted to outpatient clinics of Department ofEndocrinology and Infectious Diseases of Firat University School of Medicine between January 1st , 2014 andDecember 31st, 2014 whose urine cultures demonstrated Gram-negative bacteria were included in the study.Antibiotic susceptibilities of the isolated bacteria were determined using Vitek 2 automated system and the resultswere evaluated as sensitive and resistant. Results: In both diabetic and non-diabetic patient groups, most frequently Escherichia coli (88.5% in diabetic and85.3% in non-diabetic groups) were isolated. In the diabetic group, microorganisms mostly demonstrated the highestrates of resistance against ampicillin, cephalosporins, ciprofloxacin, amoxicillin-clavulanic acid and in the non-diabeticgroup ampicillin, amoxicillin-clavulanic acid, cefuroxime and trimethoprim-sulfamethoxazole.Conclusion: Resistance to ciprofloxacin was at a significantly higher rate in the diabetic group. In diabetic patients, itwill be more appropriate to give antibiotherapy in urinary system infections based on the antibacterial susceptibilitytest results.
Keywords: Endokrinoloji ve Metabolizma; Halk ve Çevre Sağlığı; Genel ve Dahili Tıp; Mikrobiyoloji